Measuring the User Experience of LMS CLASS-IPB Using the User Experience Questionnaire Method - Wicaksana, Arya Dimas; Juliansyah, Rizki; Lubis, Muhammad Anggi; Fami, Amata; Wahyoedi, Bontisesari (Journal of Information System and Informatics, 2024)
This study conducts the measurement of user experience (UX) of the CLASS-IPB Learning Management System (LMS) using the User Experience Questionnaire (UEQ) method. The research was carried out through several stages, including a literature review, method determination, data collection, and data analysis using UEQ Data Analysis Tools. It involved 45 students who provided feedback on six UX aspects: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Results indicated that CLASS-IPB excels in pragmatic qualities, particularly in efficiency, perspicuity, and dependability, with scores above the benchmark average. However, the system scored lower in hedonic qualities, specifically in stimulation and novelty, suggesting areas for improvement. The study concludes that while CLASS-IPB is effective in aiding task completion and user control, it needs enhancements to become more motivating and innovative.